Patrones de distribución de los Mamíferos en la Provincia Oaxaca-Tehuacanense, México - Estrada, Yiang-Qing; Luna, Rode A.; Escalante, Tania (THERYA, 2012)
We analyzed the biogeographical patterns of diversity and endemicity of the Mexican mammals, into a quadrat between 15Âº 30â€™ - 21Âº 00â€™ N latitude and 94Âº 00â€™ - 100Âº 00â€™ W longitude, in order to identify the Oaxaca-Tehuacanense province as a natural area. We analyzed the records of 133 mammalian species in databases and we modeled their distributions. Using the potential distribution models, we built a diversity map and performed an endemicity analysis. The diversity map shows an important latitudinal gradient of species richness, where the highest diversity is in boundaries of Oaxaca and Veracruz, and it can be due to the boundaries of provinces and a probable biogeographic node. The analysis of endemicity identified an area (area of consensus No. 14) with three endemic species (Habromys simulatus, Microtus quasiater and probably Megadontomys nelsoni) as biogeographic province, with boundaries wider than the Ramírez-Pulido and Castro-Campilloâ€™s (1990) Oaxaca-Tehuacanense province. We concluded that the Oaxaca-Tehuacanense province, given its pattern of richness of mammals, probably has high number of biological groups, some of them are species with restricted distribution and evolutive importance, which can be used as criteria to prioritize with efficience the conservation strategies.